2018
DOI: 10.1016/j.cnsns.2018.02.019
|View full text |Cite
|
Sign up to set email alerts
|

No nonlocality. No fractional derivative

Abstract: Abstract:The paper discusses the characteristic properties of fractional derivatives of non-integer order. It is known that derivatives of integer orders are determined by properties of differentiable functions only in an infinitely small neighborhood of the considered point. Therefore differential equation, which is considered for this point and contains a finite number of integer-order derivatives, cannot describe nonlocality in space and time. This allows us to propose a principle of nonlocality for fractio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
110
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(112 citation statements)
references
References 19 publications
0
110
0
2
Order By: Relevance
“…Several paradoxes involving the GFD with regular kernels have been pointed out in [21,14,22,5]. In [15] it has been shown that the models involving the GFD with regular kernels poorly reflect the real world data.…”
Section: Introductionmentioning
confidence: 99%
“…Several paradoxes involving the GFD with regular kernels have been pointed out in [21,14,22,5]. In [15] it has been shown that the models involving the GFD with regular kernels poorly reflect the real world data.…”
Section: Introductionmentioning
confidence: 99%
“…• there is no memory term and the approximation of the solution is obtained by using just local information; • the numerical approximation, which is obtained by means of linear interpolant polynomials, is claimed to converge to the exact solution with order 3 under the simple assumption that f (t, y(t)) is bounded. It is a well-known fact that fractional derivatives are nonlocal operators and, as discussed in some recent papers [15,16], nonlocality is an essential, distinctive and inviolable feature of fractional-order operators.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 2.11 (Fractional Gradient Descent). Let f be as in (13). Then, the left-sigmoidal fractional-order gradient method (13) converges to the true critical point t * .…”
Section: Proof Proof From (8) Integrating By Parts Yieldsmentioning
confidence: 99%